Labor Force Status Dynamics in the German Labor Market - Individual Heterogeneity and Cyclical Sensitivity - Jochen Kluve; Sandra Schaffner; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The aggregate average unemployment rate in a given country is essentially the result of individual workers' transitions between the three core labor force states, employment, unemployment, and inactivity. The dynamics of these transitions depend both, on individual duration in a particular state and the transition probabilities between states. Individual transitions, in turn, depend on observable and unobserved factors. Simultaneously, person-specific dynamics may be influenced by swings of the business cycle. This paper analyzes these labor force status dynamics for the East and West German labor market, separately using comprehensive data on monthly transitions from the SOEP. The results show that the experience of high unemployment rates is more sensitive to cyclical behavior for certain demographic groups, specifically unskilled and young workers. Heterogeneity in unemployment and transition rates differ between East and West Germany, as well as between the sexes. In East Germany, all demographic cells are almost entirely detached from the cycle. Women are less influenced by the cycle in their re-employment rate from unemployment to employment.
Keywords: E32; J21; J64; 330; Labor force; unemployment dynamics; business cycle; worker heterogeneity; Erwerbsverlauf; Arbeitslosigkeit; Erwerbstätigkeit; Konjunktur; Lebensalter; Qualifikation; Arbeitsmobilität; Deutschland